A biomechanical comparison of dominant and non-dominant arm throws for speed and accuracy - Sachlikidis, A.; Salter, C. (Sports Biomechanics, 2007)
Training a non-dominant limb may increase a competitor's ability to perform with either side of his or her body and confer an advantage over competitors that use one side of the body exclusively. The aim of this study was to determine the kinematic differences between dominant and non-dominant arm throwing techniques for speed and accuracy in Under-17 and Under-19 high-performance cricketers. Seven participants performed ten throws for each arm (dominant/non-dominant) and condition (speed/accuracy) at a target positioned 10 m in front of them. Three-dimensional kinematic variables were measured using a Vicon motion analysis system. Digital footage was used to calculate stride data, ball speed, and record target accuracy. Data were analysed using repeated-measures analysis of variance and chi-squared tests. The non-dominant arm throws had significantly lower maximum lead knee lift, did not extend the lead knee in the arm acceleration phase, had significantly less elbow flexion before extension, had significantly less shoulder external rotation at the start of the arm acceleration phase, did not have a delay between the initiation of pelvic and upper torso internal rotation, and displayed a less than optimal coordination pattern. A speed-accuracy trade-off existed for the dominant arm throws. No trade-off was identified for the non-dominant arm throws. Through an enhanced understanding of how throwing technique varies between dominant and non-dominant arms, an opportunity exists for a performance-enhancing programme to be implemented so that ambidexterity of the throwing skill can be improved.